2004
DOI: 10.4314/wsa.v29i1.4940
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous separation and determination of Tl(I) and Tl(III) by IC-ICP-OES and IC-ICP-MS

Abstract: A new hyphenated method was developed for the speciation of Tl. In this method, Tl(III) was complexed with DTPA to form a Tl(III)-DTPA anionic complex. Tl(I) did not form a complex with DTPA. The two species were separated simultaneously by means of ion chromatography using a Dionex cation exchange guard column, CG12A, and 15 mmol/l nitric acid as eluant. When ICP-OES was used as detector the detection limits for both species were 0.8 mg/l for an inert V-groove nebuliser and 0.1 mg/l for an ultrasonic nebulise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 15 publications
0
23
3
Order By: Relevance
“…The result was different from what Coetzee et al. reported. Compared with the DTPA‐free group, the addition of DTPA can significantly improve the sensitivity of both Tl species.…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…The result was different from what Coetzee et al. reported. Compared with the DTPA‐free group, the addition of DTPA can significantly improve the sensitivity of both Tl species.…”
Section: Resultscontrasting
confidence: 95%
“…The composition, concentration and the pH of mobile phase in anion HPLC system were some different from the previous reports. The result showed that the addition of DTPA in mobile phase plays a key role in separation of Tl species in both HPLC system, which is significant different from the previous reports . Compared with anion HPLC system, cation HPLC system can complete the separation in a much shorter time and the mobile phase is simpler.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Studies with binary systems, which contained a single type of Tl species and a single ligand, were carried out as preliminary determinations in order to establish the peaks associated with specific complexes in the spectra of more complex systems. The studies were not carried out at acidic pH due to the fact that Tl(I) does not form complexes with EDTA under such conditions . The corresponding peaks are presented in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…High‐performance liquid chromatography (HPLC) with electrochemical detection and inductively coupled plasma mass spectrometry (ICP‐MS) are two techniques which are often used for the determination of speciation forms of Tl. Recently, there has been an interest in the use of electrospray ionization mass spectrometry (ESI‐MS) for detection of metal cations because it has several unique advantages.…”
Section: Introductionmentioning
confidence: 99%